Real-world evidence on survival, adverse events, and health care burden in Medicare patients with mantle cell lymphoma. Issue 6 (12th May 2021) - Goyal, Ravi K.; Jain, Preetesh; Nagar, Saurabh P.; Le, Hannah; Kabadi, Shaum M.; Davis, Keith; Kaye, James A.; Du, Xianglin L.; Wang, Michael
Abstract: Most data on overall survival (OS) and adverse events (AEs) in patients with mantle cell lymphoma (MCL) are from controlled trials; therefore, in this population-based study, we retrospectively assessed treatment patterns, OS, and AEs in MCL patients initiating systemic treatment during 2013–2015 using the United States Medicare claims database. Among 1390 eligible patients (median age = 74 years), chemoimmunotherapy with bendamustine/rituximab (BR) was the preferred choice in first-line (35.3%), followed by ibrutinib (33.5%), rituximab (9.1%), and rituximab/cyclophosphamide/doxorubicin/vincristine (R-CHOP) (6.8%). Twenty-four-month OS was 73% for BR; 47%, ibrutinib; 72%, rituximab; and 71%, R-CHOP. For the four most commonly used regimens, neutropenia, anemia, hypertension, and infection were the most frequent AEs. Patients with ≥3 AEs had nearly four times higher monthly costs than those with 0–2 AEs in the first observed therapy line. Findings demonstrate a substantial increase in the economic burden as the number of AEs increased among the Medicare MCL patients.